Froude efficiency and velocity fluctuation in forearm-amputee front crawl: implications for para swimming classification - O´Dowd, D. N.; Hogarth, L.; Burkett, B.; Osborough, C.; Daly, D.; Sanders, R.; Payton, C. (Medicine & Science in Sports & Exercise, 2023)
Purpose The impact of physical impairment on Froude efficiency and intracyclic velocity fluctuation in Para swimmers is not well documented. Identification of differences in these variables between disabled and nondisabled swimmers could help develop a more objective system for assigning Para swimmers to classes for competition. This study quantifies Froude efficiency and intracyclic velocity fluctuation in unilateral forearm-amputee front crawl swimmers and evaluates associations between these variables and performance.